Use of neostigmine for the management of drug induced ileus in severe poisonings - Chan, Betty (Springer-Verlag, 2005)
INTRODUCTION: Effective whole bowel irrigation may be difficult in the presence of drug-induced ileus. Neostigmine, which inhibits the enzymatic degradation of acetylcholine, has been suggested to improve drug-induced ileus. We present two poisoning cases in which neostigmine was used to facilitate gut decontamination complicated by ileus. CASE REPORTS: A 47-year-old woman, after overdose with sodium valproate, venlafaxine, and ibuprofen, developed ileus that prevented whole bowel irrigation. Neostigmine, 2.5 mg intravenously followed by 1.25 mg three hours later, led to improved bowel transit and successful whole bowel irrigation. A 25-year-old man developed ileus after overdose with venlafaxine, dothiepin, and ethanol. Neostigmine administration led to improved intestinal motility and successful whole bowel irrigation. DISCUSSION: We demonstrate facilitated gut decontamination temporally associated with administration of neostigmine in two patients judged to have drug-induced ileus following overdose. No significant adverse events related to neostigmine were observed.